PROTECTIVE BEHAVIOUR OF RURAL CONSUMER – A CASE STUDY OF CONSUMER BEHAVIOR IN THE RURAL MARKET OF ASSAM - Prasanta, Sarmah (International Journal of Research -GRANTHAALAYAH, 2014)
Rural Marketing is a subject that has assumed much significance in contemporary Indian Economics Studies and this is quite obvious because of the huge size of rural consuming group. The vastness of Indian Rural Market has increasingly prompted many Indian as well as multi-national companies to view it as major thrust area. Unfortunately some business houses do not realize the real objectives of marketing and try to adopt all sorts of malpractices in the form of high price, deceptive practices, shoddy or unsafe products etc to serve their narrow objective of profit earning. Therefore, the rural consumer must reflect protective buying behavior in order to be free from the clutches of these sellers. In this paper an attempt has been made to examine the protective behavior of the rural consumers with the help of statistical tools like Likert scale, Chi-square test etc in order to examine the association of consumer protective behavior with variables like gender, occupation and education. And it has been found that variables namely sex, education and occupation has a bearing on the protective behavior of the consumers.